Copyright and trademark crimes in the nordic countries: analysis from the perspective of the principle of legality - Tammenlehto, Laura (Bergen journal of criminal law & criminal justice, 2020)
The principle of legality limits criminalisation in the Nordic countries. The purpose of the principle is to uphold the legitimacy of the penal authority of the state and to protect the rights of an accused by ensuring the clarity and foreseeability of the criminal law. The Nordic IPR crime provisions are extensive but determining the limits of criminalisation from them is difficult. This article focuses on the on the phrasing and style of the current Nordic copyright and trademark offences and analyses the extent to which these provisions fulfil the requirements of the principle of legality. Particular problem-causing elements in this legislation are multiple internal references and a blanket criminalisation technique combined with inaccurate definitions of objects of protection. Attention is given to three problematic aspects in the fields of copyright and trademark: copyrighted work threshold (teoskynnys/verkshöjd), moral rights, and establishing trademark through use.